DISTRIBUSI GEOGRAFIS PENYAKIT GINJAL KRONIK DI BALI: KOMPARASI FORMULA COCKCROFT-GAULT DAN FORMULA MODIFICATION OF DIET IN RENAL DISEASE - Raka Widiana, I Gde (journal of internal medicine, 2007)
Chronic kidney disease (CKD) is related to the increased of cardiovascular morbidity and mortality. Thisstudy is aiming to identify the prevalence of CKD based on demographical distribution in Bali. A communitybased study has been conducted in Bali, 1) height region among indigenous community in a village at northernpart of Bali island using cluster random samples.; 2) in urban area at Denpasar city using stratified randomsampling and 3) in isolated coastal area in Nusa Ceningan island using cluster random sampling. The glomerularfiltration rate was calculated by Cockroft-Gault (C-G) formula and abbriviated Modification of Diet in RenalDisease ringkas with 4 variables (MDRD-4). The results of GFR using both calculation were compared. CKDwas defined based on KDOQI classification, namely GFR less than 60 ml/mnt. During the study 826 sampleswere collected consisted of 219 from height region (males/females 118/101, aged 48±15 years, BW 48.9±10.4kg, creatinine 0.97±0.64 mg/dL), 302 from urban area (males/females 137/165, aged 43±16 years, BW56.1±12.1 kg, creatinine 0.81±0/.19 mg/dL) and 305 isolated coastal area (males/females 150/155, aged 42±16years, BW 53.5±10.3 kg, creatinine 1.00±0.18 mg/dL). Using C-G, mean prevalence of CKD was 56.0%(95%CI 51.2-60.7%) consisted of 69.9% (95%CI 60.6-77.9%) in height region, 61.9% (95%CI54.5-68.8%) inurban and 42.3% (95%CI 33.7-51.4%) in isolated coastal area. Using 4-MDRD formula, mean prevalence ofCKD was 6.0% ( 95%CI 1.4-18.2%) consisted of 4.8% (95%CI 0.00-31.2%) in height region, 2,6% (95%CI50.3-43.1%) in urban and 9.8% (95%CI 2.5-27.4%) in isolated coastal area. In conclusion, there is a significantdifference of CKD prevalence in Bali if calculated by C-G compared with MDRD-4. Prevalence of CKD in Baliwith MDRD-4 (6.0%) is similar to those in other countries such as USA (4.2%) and Thailand (8.8%). Whetherthe calculation of GFR using MDRD-4 is more accurate than C-G in this setting, needs further study.